Managing Factors Affecting the Professional Commitment of Primary School Teachers: A Case Study in Vinh Long Province, Vietnam - The Tuan, Phung (Cadernos de Educação Tecnologia e Sociedade, 2024)
This study focuses on the factors influencing the professional commitment of primary school teachers in Vinh Long Province, Vietnam. The primary objectives are to identify core factors, assess the current situation, and propose management measures to enhance the professional commitment of primary school teachers. The research methodology combines surveys and in-depth interviews with 900 participants, including 50 administrators and 850 primary school teachers in Vinh Long Province. The findings reveal six key factors: compensation and benefits, working environment, opportunities for training and advancement, relationships with leaders and colleagues, personal competencies, and school culture. Effective management of these factors plays a critical role in reducing turnover rates and improving educational quality. This study provides practical recommendations for educational managers and policymakers to create supportive work environments and foster long-term teacher commitment.